Outcome of Cataract Surgery on Intraocular Pressure - Zakaullah Gopang, Shabeer Ahmed Bhutto, Fayaz Ali Abassi, Naeem Akhtar Katpar, Safder Ali Abbasi, Partab Rai Nagdev (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the outcome of surgery of cataract on intraocular pressure. Study Design: Observational Study. Setting: Study carried out at Ophthalmology Department, Shaheed Mohtarma Benazir Bhutto Medical University Larkana, from 16-03-2020 to 15-09-2020. Material & Method: Patients with cataract and plan for cataract surgery were randomly taken into two groups, caliberated applanation tonometry was used to asses pre and postoperative ocular pressure. Iop range between 12-40mmHg associated with cataract patients with selected following criteria from out patient department (OPD) with 40-86 years of age, either gender, healthy cornea, having been controlled for diabetes and hypertension. Results: Age range of the patients was between 40 and 86 years, the overall mean ± SD age of the patients was 58.48 ± 9.28 years. Our study observed that female 143 (52.6%) patients were more affected than male 129 (47.4%) patients (male to female ratio was 1:1.1). Preoperative intraocular pressure ranged from 12 to 40 mm Hg; overall mean + SD intraocular pressure was 18.81 + 3.80 mmHg. While intraocular pressure checked within one week after surgery ranged from 8 to 26 mmHg, the overall mean + SD intraocular pressure was 12.41+2.24 mmHg (p value < 0.001) (table no. 2). A significant decrease in intraocular pressure was 10.49+1.020 mmHg observed at one month postoperative follow-up (p value <0.001) Conclusion: It is to be concluded that intraocular pressure decreases significantly after extraction of cataract and so the mild to moderate cataract can be treated through this as a first step in early glaucoma. Keywords: IOP, Cataract extraction, Glaucoma.